Adding vibration to high-intensity intervals increase time at high oxygen uptake in well-trained cyclists - Rønnestad, B. R.; Moen, M.; Gunnerød, S.; Øfsteng, S. (Scandinavian Journal of Medicine & Science in Sports, 2018)
The importance of accumulated time =90% of maximal oxygen consumption (VO2max) to improve performance in well-trained endurance athletes is well established. The present study compared the acute effects of adding vibrations (VIB; 40 Hz) to the work intervals during a high-intensity cycling session (HIT) with a traditional HIT session without vibration (TRAD) on time =90% of VO2max, time =90% of peak heart rate (HRpeak), electromyography (EMG) activity and mean power in well-trained cyclists (n=10, VO2max=78.6±7.4 mL·min-1·kg-1). The order of VIB and TRAD was randomized and consisted of 6x5 min work intervals performed with the highest possible mean power across the work intervals (2.5 min standardized relief periods). VIB was superior to TRAD on time =90% of VO2max, (10.99±7.00 vs. 6.95±5.28 min, respectively), time =90% of HRpeak (24.61±2.38 vs. 19.97±4.12 min, respectively) and averaged EMG activity in m. Vastus Lateralis during the work intervals (all p<0.05). The EMG/power output ratio across all work intervals was higher in VIB than TRAD (p < 0.05). Mean values across work intervals showed no difference between VIB and TRAD in mean power, rate of perceived exertion, or blood lactate concentration. Thus, the present study indicated that adding vibration to the work intervals during a HIT session can acutely increase the physiological responses of the cardiovascular system and increase time =90% VO2max and should therefore be considered in order to optimize the exercise stimulus of well-trained cyclists.